Method for preparing high-purity medical fulvic acid from low-grade coal

CN122912013APending Publication Date: 2026-10-16ANHUI FULIXIN BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611073730.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]为了克服背景技术中指出的现有提取方法存在的黄腐酸纯度低、活性结构易破坏、生物安全性差及难以满足医用标准等关键缺陷,本发明公开了一种以低级别煤为原料制取高纯度医用黄腐酸的方法,旨在提供一种集温和氧化降解、高效定向提取与多级精细纯化于一体的稳定制备工艺

Benefits of technology

[0024] 1. High product purity and superior quality: Through multi-stage fine purification, ash, pigments and macromolecular inert substances in the coal source are effectively removed, resulting in significantly improved purity of potassium humate, lighter color and better solubility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912013A_ABST
    Figure CN122912013A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing high-purity medical fulvic acid from low-grade coal, aiming at solving the problems of low product purity, poor biological safety and difficult guarantee of activity in the prior art. The method comprises the following steps: mixing lignite or weathered coal powder with dilute alkali solution for pretreatment, and then performing mild oxidative degradation on the lignite or weathered coal powder under the assistance of ultrasonic waves by using hydrogen peroxide; obtaining a crude fulvic acid solution by acid precipitation of a reaction solution; then, performing liquid-liquid extraction on the crude fulvic acid solution by using ethyl acetate to remove fat-soluble impurities, and then performing deep purification and potassium salt transformation on the crude fulvic acid solution by using salt water backwashing and potassium hydroxide ethanol solution back extraction; and finally, obtaining a final product by performing vacuum concentration and spray drying or freeze drying. Through the synergistic process of "oxidative degradation-multistage solvent purification-salt transformation", the high-purity potassium fulvate with the fulvic acid content of greater than or equal to 95%, the ash content of less than or equal to 2% and the heavy metal content far lower than the medical standard can be stably prepared from the low-quality coal source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coal deep processing and natural product extraction technology, specifically relating to a method for producing high-purity, high-biosafety fulvic acid from low-grade coal (such as lignite and weathered coal), and particularly a method for preparing medical-grade potassium fulvicate suitable for the pharmaceutical and health product fields. Background Technology

[0002] Fulvic acid, as a humic acid component with small molecular weight and high activity, exhibits various physiological activities in the pharmaceutical field, including anti-inflammatory, antiviral, immunomodulatory, and wound-healing promotion, and has broad prospects for medical development. However, existing fulvic acid products extracted from coal generally suffer from low purity, high impurity content, and poor biosafety, making it difficult to meet stringent medical standards.

[0003] Currently, traditional methods for extracting fulvic acid from low-grade coal (such as lignite and weathered coal) have significant technical limitations: First, while the alkali-dissolution-acid-precipitation method, as the mainstream process, can effectively extract total humic acid, its separation targeting is poor, and the purity of the obtained fulvic acid is generally below 60%. Furthermore, residual coal tar, heavy metals, and other impurities may introduce biotoxicity risks. Second, the extraction process often uses strong acids and strong bases under harsh conditions, which, while increasing the extraction rate, easily damages the natural active structure of fulvic acid and may lead to harmful solvent residues. Third, conventional purification techniques (such as single-solvent extraction) have limited effectiveness in removing impurities such as pigments and ash with similar molecular weights, making it difficult to effectively enrich fulvic acid and deeply remove harmful impurities, resulting in products with dark color and high ash content that cannot meet the purity requirements for medical use.

[0004] Furthermore, existing technologies primarily focus on the production of agricultural or industrial-grade humic acid. Their process design is highly dependent on the quality of raw coal and lacks refined control over the biosafety of medical-grade products. Harmful elements such as heavy metals and arsenic in the raw materials, if not specifically purified, will directly lead to substandard products. Insufficient purification also carries the risk of solvent residue or incomplete conversion in the final product, affecting its pharmaceutical safety. Therefore, existing technological systems struggle to reliably convert low-quality coal sources into high-purity, low-toxicity, and safe medical-grade humic acid.

[0005] In summary, existing technologies cannot simultaneously achieve high purity and high biosafety while ensuring the bioactivity of fulvic acid, which has become a key technological bottleneck restricting its application in the pharmaceutical field. Therefore, there is an urgent need to develop an innovative method that can be adapted to low-grade coal raw materials, and through mild and efficient directional conversion and multi-stage fine purification, ultimately stably prepare high-purity fulvic acid that meets medical standards. Summary of the Invention

[0006] To overcome the key shortcomings of existing extraction methods as mentioned in the background art, such as low purity of fulvic acid, easy destruction of active structures, poor biosafety, and difficulty in meeting medical standards, this invention discloses a method for producing high-purity medical-grade fulvic acid from low-grade coal. The aim is to provide a stable preparation process integrating mild oxidative degradation, efficient targeted extraction, and multi-stage fine purification. This technology, through targeted oxidation activation and composite solvent purification strategies, achieves high-yield production of high-purity, high-activity, low-toxicity, and safe medical-grade fulvic acid from low-quality coal sources, providing a reliable raw material guarantee for its application in the pharmaceutical and health product fields.

[0007] To achieve the above objectives, the present invention includes the following technical solutions.

[0008] A method for producing high-purity medical-grade fulvic acid from low-grade coal includes the following steps:

[0009] (1) Raw material pretreatment and oxidative degradation: Lignite or weathered coal with a particle size of less than 100 mesh is mixed with sodium hydroxide solution with a mass fraction of 0.5%-2% at a solid-liquid ratio of 1:8-1:15 (g / mL), and stirred at 60-80℃ and normal pressure for 1-2 hours to obtain coal sample slurry; then 10%-20% of the dry weight of the coal sample of hydrogen peroxide is slowly added to the slurry, and stirred at 50-70℃ for 2-4 hours to carry out oxidative degradation;

[0010] (2) Acid precipitation and solid-liquid separation: The pH value of the reaction solution obtained in step (1) is adjusted to 2.0-3.0 with hydrochloric acid or sulfuric acid with a mass fraction of 10%-20%, and allowed to stand for 12-24 hours to allow humic acid to fully precipitate; then solid-liquid separation is carried out, and the supernatant is collected, which is the crude fulvic acid solution.

[0011] (3) Primary purification: Add 1 / 5 to 1 / 3 of the volume of ethyl acetate to the crude fulvic acid solution obtained in step (2), extract, allow to stand and separate into layers, and collect the upper organic phase;

[0012] (4) Secondary purification and transformation: Add 1 / 10-1 / 5 of the volume of saturated sodium chloride solution to the organic phase obtained in step (3) for backwashing and discard the aqueous phase; then add 1%-5% potassium hydroxide ethanol solution by mass fraction to the organic phase for back-extraction until the pH value of the aqueous phase reaches 7.0-8.0 and collect the aqueous phase;

[0013] (5) Concentration and drying: The aqueous phase obtained in step (4) is concentrated under reduced pressure at 50-65℃ and -0.08 ~ -0.1 MPa to obtain potassium humate concentrate; then spray drying or vacuum freeze drying is performed to obtain high-purity medical potassium humate powder.

[0014] Furthermore, in the above method, in step (1), the lignite is young lignite with a humic acid content of not less than 5%, and the weathered coal has a humic acid content of not less than 15%.

[0015] Furthermore, in the above method, in step (1), the hydrogen peroxide is added by dripping, and the dripping time is controlled to be 30-60 minutes. The oxidative degradation reaction is carried out under ultrasonic assistance, with an ultrasonic power of 300-500W and a frequency of 25-40kHz.

[0016] Furthermore, in step (2) of the above method, the acid precipitation process is carried out by adding acid dropwise, accompanied by low-speed stirring, and the dropping rate is controlled to be 1-2 mL / min.

[0017] Furthermore, in the above method, in step (3), the extraction process is repeated 2-3 times to combine all organic phases.

[0018] Furthermore, in the above method, in step (4), the volume fraction of ethanol in the potassium hydroxide ethanol solution is 60%-80%.

[0019] Furthermore, in the above method, in step (5), the inlet air temperature of the spray drying is 150-180℃ and the outlet air temperature is 70-90℃; the cold trap temperature of the vacuum freeze dryer is below -45℃, the drying chamber pressure is below 10 Pa, and the material thickness is not more than 1cm.

[0020] The present invention also discloses a high-purity medical fulvic acid product prepared by the above method. The product is potassium fulvicate with a fulvic acid content ≥95%, ash content ≤2%, total heavy metal content ≤10 ppm, arsenic content ≤2 ppm, and lead content ≤3 ppm, which meets the purity requirements of medical excipients or functional ingredients.

[0021] This invention also discloses the application of the above-mentioned high-purity medical fulvic acid product in the preparation of drugs with anti-inflammatory, antioxidant or immunomodulatory functions.

[0022] Furthermore, in the above applications, the dosage form of the drug is an oral liquid, capsule, tablet, or granule.

[0023] Compared with the prior art, the present invention has the following outstanding advantages:

[0024] 1. High product purity and superior quality: Through multi-stage fine purification, ash, pigments and macromolecular inert substances in the coal source are effectively removed, resulting in significantly improved purity of potassium humate, lighter color and better solubility.

[0025] 2. Good biosafety: It has been specifically and deeply removed from harmful impurities such as heavy metals and arsenic. The product meets or even exceeds the impurity control requirements of medical raw materials / excipients, and has high application safety.

[0026] 3. Excellent Activity Retention and Stability: Mild oxidation and purification conditions maximize the protection of the natural active structure of fulvic acid, and in vitro antioxidant experiments confirm its excellent activity. After conversion to the potassium salt form, the product's physicochemical stability is far superior to that of acidic fulvic acid, facilitating storage and formulation.

[0027] 4. Strong process adaptability: This method is well applicable to low-grade coal raw materials of different qualities, and can efficiently transform low-value resources into high-value-added medical products. The process route is clear and easy to scale up for industrialization. Attached Figure Description

[0028] Figure 1 Comparison of purity (%) of products obtained by different preparation methods in Test Example 1;

[0029] Figure 2 Comparison of ash content (%) of products obtained by different preparation methods in Test Example 2

[0030] Figure 3 Comparison of total heavy metal content (ppm) in products obtained by different preparation methods in Test Example 2. Detailed Implementation

[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] Table 1 Raw Material List

[0033] Raw material name Specifications / parameter requirements Source / Acquisition Method lignite Young lignite, particle size <100 mesh, humic acid content ≥5%. Young lignite from Xilingol League, Inner Mongolia, is crushed, ground, and sieved before use. Weathered coal Particle size < 100 mesh, humic acid content ≥ 15% Weathered coal from Datong, Shanxi Province, is crushed, ground, and sieved before use. Sodium hydroxide Analytical grade (AR), purity ≥96%. Commercially available chemical reagents hydrogen peroxide Food grade or pharmaceutical grade, concentration 30% (w / w) Commercially available hydrogen peroxide solution hydrochloric acid Analytical grade (AR), concentration 36%–38%. Commercially available chemical reagents for pH adjustment sulfuric acid Analytical grade (AR), concentration 95%~98%. Commercially available chemical reagents can be used as alternatives to hydrochloric acid for pH adjustment. Ethyl acetate Analytical Pure (AR) Commercially available chemical reagents for liquid-liquid extraction Sodium chloride Analytical Pure (AR) Commercially available chemical reagents used to prepare saturated saline solution for backwashing. potassium hydroxide Analytical grade (AR), purity ≥85%. Commercially available chemical reagents used for back-extraction and salt conversion. Anhydrous ethanol Analytical Pure (AR) Commercially available chemical reagents used to prepare potassium hydroxide ethanol solution.

[0034] Example 1

[0035] A method for producing high-purity medical-grade fulvic acid from low-grade coal, the specific steps of which are as follows:

[0036] (1) Raw material pretreatment and oxidative degradation: Weigh 100g of young lignite with a particle size of less than 100 mesh and a humic acid content of about 8%, mix it with 1200mL of 0.8% sodium hydroxide solution (solid-liquid ratio 1:12), and stir and react for 1.5 hours at 70℃ and normal pressure to obtain coal sample slurry; then use a constant pressure dropping funnel to slowly add 15g (15wt%) of hydrogen peroxide to the above slurry over 60 minutes, and continue stirring and reacting for 3 hours at 60℃ and 400W ultrasound (frequency 28kHz);

[0037] (2) Acid precipitation and solid-liquid separation: The pH of the reaction solution obtained in step (1) was slowly adjusted to 2.5 with 15% hydrochloric acid and allowed to stand for 18 hours; then it was centrifuged at 5000 r / min for 15 minutes, and the supernatant was collected to obtain about 980 mL of crude fulvic acid solution.

[0038] (3) Primary purification: Add 250 mL of ethyl acetate to the crude fulvic acid solution obtained in step (2), place it in a separatory funnel and shake vigorously for 5 minutes. After standing and separating the layers, collect the upper organic phase. Repeat this extraction process once and combine the organic phases from both extractions. The total volume is approximately 480 mL.

[0039] (4) Secondary purification and transformation: Add 50 mL of saturated sodium chloride solution to the combined organic phase, gently shake and wash for 30 seconds, let stand for layering, and discard the lower aqueous phase; then slowly add 1.5% potassium hydroxide ethanol solution (70% ethanol volume fraction) to the organic phase for back extraction until the pH of the aqueous phase stabilizes at 7.5, collect the aqueous phase, and obtain about 180 mL of potassium humate aqueous solution;

[0040] (5) Concentration and drying: The aqueous phase obtained in step (4) is concentrated under reduced pressure at 60°C and -0.09 MPa to obtain about 45 mL of potassium humate concentrate; then spray drying is performed (inlet air temperature 160°C, outlet air temperature 80°C) to obtain 12.1 g of high-purity medical potassium humate product in brownish-yellow powder form.

[0041] The product of this embodiment contains 96.2% fulvic acid, 1.5% ash, 8 ppm total heavy metals, 1.5 ppm arsenic, and 2.2 ppm lead.

[0042] Example 2

[0043] A method for producing high-purity medical-grade fulvic acid from low-grade coal, the specific steps of which are as follows:

[0044] (1) Raw material pretreatment and oxidative degradation: Weigh 100g of weathered coal with a particle size of less than 100 mesh and a humic acid content of about 18%, mix it with 1000mL of 1.2% sodium hydroxide solution (solid-liquid ratio 1:10), and stir and react for 2 hours at 65℃ and normal pressure; then slowly add 12g (12wt%) of hydrogen peroxide dropwise over 50 minutes, and continue stirring and reacting for 2.5 hours at 55℃ and 350W ultrasound (frequency 33kHz);

[0045] (2) Acid precipitation and solid-liquid separation: The pH of the reaction solution obtained in step (1) was adjusted to 2.8 with 12% sulfuric acid and allowed to stand for 15 hours; centrifugation was performed and the supernatant was collected in about 890 mL.

[0046] (3) Primary purification: Add 300 mL of ethyl acetate to the supernatant, extract twice, and combine the organic phases to approximately 560 mL;

[0047] (4) Secondary purification and transformation: After backwashing the organic phase with 60 mL of saturated sodium chloride solution, back-extract with 2% potassium hydroxide ethanol solution (ethanol volume fraction 65%) until the aqueous phase pH=7.2, and collect about 220 mL of aqueous phase;

[0048] (5) Concentration and drying: After the aqueous phase is concentrated under reduced pressure at 55°C, it is then freeze-dried under vacuum (cold trap temperature -50°C, drying chamber pressure 8 Pa) to obtain 20.5g of light yellow flocculent product.

[0049] Testing revealed that the product in this embodiment contained 97.8% fulvic acid, 1.1% ash, 6 ppm total heavy metals, 1.1 ppm arsenic, and 1.8 ppm lead.

[0050] Example 3

[0051] A method for producing high-purity medical-grade fulvic acid from low-grade coal, the specific steps of which are as follows:

[0052] (1) Raw material pretreatment and oxidative degradation: Weigh 100g of young lignite with a particle size of less than 100 mesh, mix it with 1500mL of 1.5% sodium hydroxide solution (solid-liquid ratio 1:15), and stir at 75℃ for 1 hour; then slowly add 20g (20wt%) of hydrogen peroxide over 70 minutes, and continue stirring for 4 hours at 65℃ and 450W ultrasound (frequency 25kHz).

[0053] (2) Acid precipitation and solid-liquid separation: Adjust the pH value to 2.2 with 18% hydrochloric acid, let stand and age for 20 hours; centrifuge and collect about 1250 mL of supernatant;

[0054] (3) Primary purification: Add 400 mL of ethyl acetate to the supernatant, extract three times, and combine the organic phases to approximately 1050 mL;

[0055] (4) Secondary purification and transformation: After backwashing with 100 mL of saturated sodium chloride solution, back-extract with 2.5% potassium hydroxide ethanol solution (ethanol volume fraction 75%) until the aqueous phase pH=7.8, and collect about 260 mL of aqueous phase;

[0056] (5) Concentration and drying: The aqueous phase was concentrated under reduced pressure at 65°C and then spray-dried (inlet air temperature 170°C, outlet air temperature 85°C) to obtain 14.8g of yellow-brown powder product.

[0057] Testing revealed that the product in this embodiment contained 95.5% fulvic acid, 1.8% ash, 9 ppm total heavy metals, 1.8 ppm arsenic, and 2.5 ppm lead.

[0058] Comparative Example 1

[0059] A method for preparing fulvic acid is basically the same as that in Example 2, except that hydrogen peroxide is not added for oxidative degradation in step (1). After extraction with alkaline solution at 65°C for 2 hours, subsequent acid precipitation and other steps are carried out directly.

[0060] Results: The final product was dark brown to black, with a fulvic acid content of only 58.3% and an ash content as high as 15.7%. The solution was turbid after dissolution and contained obvious insoluble matter.

[0061] Comparative Example 2

[0062] A method for preparing fulvic acid is basically the same as that in Example 2, except that the ethyl acetate extraction and backwashing, and back-extraction purification steps in steps (3) and (4) are omitted. After obtaining the supernatant by acid precipitation in step (2), the supernatant is directly concentrated and dried.

[0063] Results: The final product was dark black in color, with a fulvic acid content of 72.1%, an ash content as high as 8.9%, and a total heavy metal content of 35 ppm, far exceeding medical standards.

[0064] Comparative Example 3

[0065] A method for preparing fulvic acid, the steps of which are basically the same as those in Example 2, the difference being that in step (4), potassium hydroxide ethanol solution is not used for back-extraction transformation, but the ethyl acetate extract phase obtained in step (3) is directly concentrated and dried in an attempt to obtain acidic fulvic acid.

[0066] Results: The product obtained was a dark, viscous paste that was highly hygroscopic, difficult to pulverize into a stable powder, and had excessive solvent residue.

[0067] Comparative Example 4

[0068] A method for preparing fulvic acid using the traditional strong acid-strong alkali method. Specifically, weathered coal is extracted with 5% sodium hydroxide solution at 95°C with vigorous stirring for 2 hours. After acid precipitation, the obtained crude humic acid is complexed and extracted with 5% sodium pyrophosphate solution in a boiling water bath for 1 hour. After acid precipitation again, the supernatant is collected, concentrated, and dried.

[0069] Results: The method has a long process and high energy consumption. The final product has a fulvic acid content of 81.5%, low activity, and the ash and heavy metal content did not reach the levels of the example.

[0070] Test Example 1

[0071] Product core purity and yield testing

[0072] Objective: To verify the advantages of the method of the present invention (Examples 1-3) over traditional or simplified processes (Comparative Examples 1-4) in terms of the purity and yield of the final product fulvic acid.

[0073] method:

[0074] Purity determination: Referring to the general chapter of Part IV of the Chinese Pharmacopoeia, the content of fulvic acid in the aqueous solution of the final product of each example and comparative example was determined by ultraviolet-visible spectrophotometry at a wavelength of 465 nm, and the mass fraction was calculated.

[0075] Yield Calculation: The mass yield of the final dried potassium humate product is calculated based on the dry basis mass of the raw coal (lignite or weathered coal) used.

[0076] Results: The results are shown in Table 1 and... Figure 1 .

[0077] Table 1: Comparison of purity and yield of products obtained by different preparation methods.

[0078] Group Content (%, w / w) of fulvic acid Product yield (%, based on dry coal) Example 1 96.2 12.1 Example 2 97.8 20.5 Example 3 95.5 14.8 Comparative Example 1 58.3 15.6 Comparative Example 2 72.1 18.9 Comparative Example 3 81.5 16.2 Comparative Example 4 90.5* 22.1*

[0079] Note: The product in Comparative Example 4 is an unstable paste. Its purity and yield are estimated values ​​and have limitations in practical application.

[0080] Conclusion: The products prepared by the methods in Examples 1-3 of this invention all exhibited a stable fulvic acid purity of over 95%, significantly higher than that of the comparative examples. Comparative Example 1 (without oxidative degradation) showed the lowest purity, demonstrating that the oxidation step is crucial for breaking down the macromolecular structure and releasing fulvic acid. Comparative Example 2 (solvent-free purification) showed insufficient purity, indicating that multi-stage solvent purification is key to removing pigments and ash and achieving high purity. This invention achieves a reasonable product yield while ensuring high purity.

[0081] Test Example 2

[0082] Key impurities and biosafety index testing

[0083] Objective: To evaluate the effectiveness of the method of the present invention in removing harmful impurities (ash, heavy metals) and to prove that its product meets medical requirements.

[0084] method:

[0085] Ash content determination: The ash content was determined by the residue on ignition test method according to General Chapter 2301 of Part IV of the Chinese Pharmacopoeia.

[0086] Determination of heavy metal content: Inductively coupled plasma mass spectrometry (ICP-MS) was used to determine the total amount of arsenic (As), lead (Pb) and heavy metals in the product.

[0087] Results: The results are shown in Table 2 and... Figure 2 and Figure 3 .

[0088] Table 2: Content of key impurities in products obtained by different preparation methods.

[0089] Group Ash content (%) Total heavy metals (ppm) Arsenic (As, ppm) Lead (Pb, ppm) Example 1 1.5 8 1.5 2.2 Example 2 1.1 6 1.1 1.8 Example 3 1.8 9 1.8 2.5 Comparative Example 1 15.7 45 5.2 8.9 Comparative Example 2 8.9 35 4.1 6.5 Comparative Example 3 5.2 28 3.0 4.8 Medical Reference Standards ≤3.0 ≤20 ≤2 ≤5

[0090] Conclusion: The impurity content of the products in the embodiments of this invention is significantly lower than that in the comparative example, and meets or exceeds the control requirements for related impurities in common medical excipients / raw materials. This proves that the "oxidative degradation + multi-stage solvent purification" process of this invention is necessary and effective for the deep removal of harmful impurities from low-grade coal and for ensuring the biosafety of the products.

[0091] Test Example 3

[0092] Verification of the necessity of process steps

[0093] Objective: To verify the contribution of each step in a multi-stage purification process by comparing different purification pathways.

[0094] method:

[0095] Three groups of samples were prepared:

[0096] Group A: Prepared according to the method in Example 2.

[0097] Group B: Only ethyl acetate extraction (i.e., step 3) is performed, omitting the subsequent salt washing and back-extraction conversion.

[0098] Group C: Ethyl acetate extraction is omitted, and the acid-precipitated supernatant is directly washed with salt and back-extracted (assuming feasibility).

[0099] Compare the appearance, solubility, and fulvic acid content of the three final products.

[0100] Results: The results are shown in Table 3.

[0101] Table 3: Comparison of the effects of different purification routes

[0102] Group Process Flow Product Appearance Solubility Content (%, w / w) of fulvic acid A Complete process (Example 2) light yellow powder clarify 97.8 B Extraction only, no transformation Dark brown viscous substance turbid 85.4 C No extraction, direct back-extraction (trial) Black insoluble matter Difference Unable to measure accurately

[0103] Conclusion: Ethyl acetate extraction (primary purification) effectively removed most of the fat-soluble pigments and some macromolecular impurities, which is key to obtaining a light-colored product. Subsequent salt washing and back-extraction (secondary purification) further removed water-soluble ash and achieved the conversion to stable potassium salts, jointly ensuring the high purity and excellent physicochemical properties of the final product. The desired effect of this invention cannot be achieved without any of these steps.

[0104] Test Example 4

[0105] Product stability assessment

[0106] Objective: To investigate the stability of the product of this invention (potassium fulvic acid) under accelerated testing conditions and compare it with acidic fulvic acid (product of Comparative Example 3).

[0107] method:

[0108] The product powders from Example 2 and Comparative Example 3 were placed in open petri dishes and then placed in a constant temperature and humidity chamber at 40±2℃ and 75±5% relative humidity for 10 days. Samples were taken on days 0, 5, and 10 to observe the appearance and determine the moisture content and fulvic acid content.

[0109] Results: The results are shown in Table 4.

[0110] Table 4: Comparison of Product Stability under Accelerated Testing Conditions

[0111] Group Time (days) Appearance changes Increase in water content (%) The content of fulvic acid decreased by (%) Example 2 0 Light yellow powder, loose - 0 Example 2 5 Slightly darker in color, still loose +0.8 -1.2 Example 2 10 The color has darkened, and there is slight clumping. +1.5 -2.5 Comparative Example 3 0 Dark brown paste, viscous - 0 Comparative Example 3 5 It absorbs moisture severely and clumps together. +15.3 -8.7 Comparative Example 3 10 Turned into a dark black viscous liquid +32.1 -15.4

[0112] Conclusion: The potassium fulvate product prepared by this invention exhibits excellent physical and chemical stability, with minimal changes under accelerated conditions. In contrast, the acidic fulvate product of Comparative Example 3 is highly hygroscopic, clumps, and its content decreases rapidly, demonstrating that converting it to salt form is a necessary means to ensure its stability as a medical raw material.

[0113] Test Example 5

[0114] In vitro antioxidant activity evaluation

[0115] Objective: To verify whether high-purity potassium humate products retain their inherent biological activity.

[0116] method:

[0117] Different concentrations of aqueous solutions of the product from Example 2 were prepared, and its antioxidant activity was determined using the DPPH free radical scavenging method with ascorbic acid (Vc) as a positive control. The half-maximal scavenging concentration (IC50) was calculated.

[0118] result:

[0119] Example 2: The IC50 value of the product against DPPH radicals was 0.12 ± 0.02 mg / mL.

[0120] The IC50 value of the positive control vitamin C was 0.08 ± 0.01 mg / mL.

[0121] The IC50 value of Comparative Example 2 (72.1% purity) was 0.25 ± 0.03 mg / mL.

[0122] Conclusion: The high-purity potassium humate prepared by this invention exhibits significant DPPH free radical scavenging ability, with activity superior to low-purity products and comparable to the positive control vitamin C. This demonstrates that the purification process of this invention effectively preserves or even concentrates the active functional groups of humic acid while improving purity, providing an active basis for its pharmaceutical applications.

[0123] Test Example 6

[0124] Raw material adaptability test

[0125] Objective: To verify the applicability of the method of the present invention to low-grade coal raw materials of different sources and qualities.

[0126] method:

[0127] Three types of lignite / weathered coal from different origins with different initial humic acid contents (A: 5%, B: 12%, C: 20%) were selected and prepared strictly according to the process flow of Example 2.

[0128] Results: The results are shown in Table 5.

[0129] Table 5: Results of applying the method of the present invention to different raw materials

[0130] raw coal Initial fulvic acid content (%) The content of fulvic acid in the final product (%) Product yield (%) Coal A 5 95.1 5.5 Coal B 12 96.5 12.8 Coal C 20 97.8 20.5

[0131] Conclusion: The method of this invention is well adaptable to low-grade coals of varying qualities. Although the initial fulvic acid content of the raw materials affects the final yield, the process of this invention can consistently produce medical-grade products with a purity higher than 95%, demonstrating the versatility and reliability of the process.

[0132] Test Case Summary:

[0133] The systematic verification through the above series of test examples fully demonstrates the significant progress and synergistic effect of the technical solution of this invention compared with existing or simplified methods. The core data from Test Examples 1 and 2 show that the method of this invention can stably prepare products with a fulvic acid content higher than 95% and extremely low levels of key impurities (ash, heavy metals, etc.), fully meeting medical requirements. This effect is the result of the indispensable and combined effects of steps such as "oxidative degradation," "solvent extraction," and "salt washing transformation." Test Example 3 further breaks down and confirms the unique contribution and necessity of each purification step. Test Example 4, through accelerated stability experiments, clarifies the crucial role of converting the product into potassium fulvic acid salt in ensuring its stability as a pharmaceutical raw material. The activity evaluation of Test Example 5 confirms that the purification process of this invention, while improving purity, not only does not destroy its biological activity, but also enriches active functional groups due to the effective removal of impurities, exhibiting strong in vitro antioxidant capacity. Finally, Test Example 6 demonstrates that the process of this invention has good universality for raw materials, broadening the pathways for the high-value utilization of low-grade coal. In summary, all test cases support each other, demonstrating that the present invention successfully transforms low-grade coal into a stable medical product with high purity, high safety, and high activity, achieving a unity of methodological inventiveness, product practicality, and application foresight.

Claims

1. A method for producing high-purity medical-grade fulvic acid from low-grade coal, characterized in that, Includes the following steps: (1) Raw material pretreatment and oxidative degradation: Lignite or weathered coal with a particle size of less than 100 mesh is mixed with sodium hydroxide solution with a mass fraction of 0.5%-2% at a solid-liquid ratio of 1:8-1:15 (g / mL), and stirred at 60-80℃ and normal pressure for 1-2 hours to obtain coal sample slurry; then 10%-20% of the dry weight of the coal sample of hydrogen peroxide is slowly added to the slurry, and stirred at 50-70℃ for 2-4 hours to carry out oxidative degradation; (2) Acid precipitation and solid-liquid separation: The pH value of the reaction solution obtained in step (1) is adjusted to 2.0-3.0 with hydrochloric acid or sulfuric acid with a mass fraction of 10%-20%, and allowed to stand for 12-24 hours to allow humic acid to fully precipitate; then solid-liquid separation is carried out, and the supernatant is collected, which is the crude fulvic acid solution. (3) Primary purification: Add 1 / 5 to 1 / 3 of the volume of ethyl acetate to the crude fulvic acid solution obtained in step (2), extract, allow to stand and separate into layers, and collect the upper organic phase; (4) Secondary purification and transformation: Add 1 / 10-1 / 5 of the volume of saturated sodium chloride solution to the organic phase obtained in step (3) for backwashing and discard the aqueous phase; then add 1%-5% potassium hydroxide ethanol solution by mass fraction to the organic phase for back-extraction until the pH value of the aqueous phase reaches 7.0-8.0 and collect the aqueous phase; (5) Concentration and drying: The aqueous phase obtained in step (4) is concentrated under reduced pressure at 50-65℃ and -0.08 ~ -0.1 MPa to obtain potassium humate concentrate; then spray drying or vacuum freeze drying is performed to obtain high-purity medical potassium humate powder.

2. The method according to claim 1, characterized in that: In step (1), the lignite is young lignite with a humic acid content of not less than 5%, and the weathered coal has a humic acid content of not less than 15%.

3. The method according to claim 1, characterized in that: In step (1), the hydrogen peroxide is added by dripping, and the dripping time is controlled to be 30-60 minutes. The oxidative degradation reaction is carried out under ultrasonic assistance, with an ultrasonic power of 300-500W and a frequency of 25-40kHz.

4. The method according to claim 1, characterized in that: In step (2), the acid precipitation process is carried out by adding acid dropwise, accompanied by low-speed stirring, and the dropping rate is controlled to be 1-2 mL / min.

5. The method according to claim 1, characterized in that: In step (3), the extraction process is repeated 2-3 times to combine all organic phases.

6. The method according to claim 1, characterized in that: In step (4), the volume fraction of ethanol in the potassium hydroxide ethanol solution is 60%-80%.

7. The method according to claim 1, characterized in that: In step (5), the inlet air temperature of the spray dryer is 150-180℃ and the outlet air temperature is 70-90℃; the cold trap temperature of the vacuum freeze dryer is below -45℃, the drying chamber pressure is below 10 Pa, and the material thickness is not more than 1cm.

8. The high-purity medical-grade fulvic acid product prepared by the method according to any one of claims 1-7, characterized in that: The product is potassium fulvate, with a fulvic acid content ≥95%, ash content ≤2%, total heavy metal content ≤10 ppm, arsenic content ≤2 ppm, and lead content ≤3 ppm, meeting the purity requirements for medical excipients or functional ingredients.

9. The use of the high-purity medical fulvic acid product as described in claim 8 in the preparation of drugs with anti-inflammatory, antioxidant or immunomodulatory functions.

10. The application according to claim 9, characterized in that: The dosage form of the drug is oral liquid, capsule, tablet or granule.